PENGARUH KEPEMIMPINAN DAN MOTIVASI TERHADAP IMPLEMENTASI SISTEM MANAJEMEN MUTU DAN KINERJA PT. PEC-TECH SERVICES INDONESIA DI PANGKALAN KERINCI - Edwin, Muhammad (Jurnal Tepak Manajemen Bisnis, 2015)
This study aims to determine the contribution of leadership, motivation and quality management system to performance of PT. PEC-Tech Services Indonesia at Pangkalan Kerinci.The method used is survey method, while the population in this study were 7(seven) department in the PT. PEC-Tech Services Indonesia that amounting to 1,523 (one thousand five hundred twenty three) ,They were Harvesting Department (445 people), Log Transport Department (346 people), Heavy Equipment Department (81 people), Woodyard Department (89 people), Crane Department (88 people), Workshop Department (388 people) and Supporting Department (86 People). Relatively number of relatively large population, the sample set as many as 94 people of population by10% precision and confidence90% level. Hypothesis testing is done using path analysis and to explain the relationship variables were analyzed using SPSS 17.0 statistical test program for windows.The results showed that simultaneous variable of leadership and motivation significantly influence the quality management system and performance in PT. PEC-Tech Service Indonesia at Pangkalan Kerinci. This is evidence by their significant value less than 0.05 (Î± = 5%). This means the study received the hypothesis that leadership and motivation also affect the performance through quality management system implementation in PT. PEC-Tech Services Indonesia at Pangkalan Kerinci.Keyword: Leadership, Motivation, Quality Management System, Performance.